A Musician from Elsewhere in Quest of Knowledge: Past and Present in Armas Launis’ Ideas on the North African Musical Traditions - Helena TYRVÄINEN (Turath)
In 1910, composer, musicologist and writer Armas Launis (Hämeenlinna, Finland 1884–Nice 1959) was the first Finn to have defended a doctoral dissertation within the discipline of Musicology. Already quite experienced in field work among rural populations when he settled in Algiers in the 1920s, he enhanced his knowledge about local music traditions not only through personal observation and by interviewing local musicians (Yafil, Mahieddine) and other residents, but also from scholarly writings and other literary sources. I investigate how impulses from earlier thought and Launis’s practical experiences shaped his ideas on Maghrebi music. As my source, I use his travel book from 1927, Murjaanien maassa (In the land of the Moors), his first extensive interpretation of the cultures of the Maghreb, as well as his university lecture from 1928, Piirteitä maurilais-arabialaisesta musiikista (Traits of the Arabo-Moorish music). The idea of the ongoing presence of ancientness in modern times holds a central place in Launis’s thinking about North African music. When claiming that the evolution of the North African musical traditions had ended, he did not necessarily lean on western ideas only. Launis never proposed a scientific interpretation of the music traditions of the Maghreb area. However, his position extends to his subsequent output as an opera composer.